http://edissertations.nottingham.ac.uk/deposit.html - LIU, WENCHAO (2022)
The basic characteristics of omni-channel retailing dictate that the difficulty of logistics is slowly rising. The purpose of this dissertation is to analyse the different channel return logistics barriers in omni-channel retailing scenarios and to discuss how return logistics service quality affects consumers' perceived value as well as their satisfaction and loyalty. Moreover, different perspectives are summarised regarding the development of omni-channel retailing, the impact of omni-channel retail logistics, and the service quality of omni-channel return logistics. Based on a literature review that summarises consumer perceived value, consumer expertise, consumer satisfaction, and consumer loyalty, a relationship between service quality and consumer perceived value in return logistics is constructed. From the well-established service quality scale, four aspects were differentiated, which are assurance quality, convenience quality, empathizing quality, order discrepancy handling quality. Furthermore, this dissertation tested the entire model path. The results of the test tell us that all four hypotheses can be successfully supported. While expertise has no moderating effect on previous quality and order variation, we concluded that consumer perceived value can positively influence consumer satisfaction, and at the same time, when positively influenced, consumer satisfaction positively contributes to the formation of consumer loyalty. Finally, relevant suggestions are put forward for omni-channel retail theory and practitioners.